PEMANFAATAN TEKNOLOGI PEMBELAJARAN UNTUK MENINGKATKAN KUALITAS PENDIDIKAN - FAISAL - (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2010)
management and evaluation, process and source to learn. Technology has enabled existence of speed value and improvement quality of study at education institute which at a few last years still was dream. We have seen how education institute has exploited strength of technology to build an education graduate and service which more certifiable for the cutomer? clients. This thing means that technology to bring us is more thinking much ofly and enjoys benefit from study and work.Technological progress gives opportunity to do study activity when and it doesn't matter, this thing means that study activity can happened at place and the same time or at place and different time